Identification of a prognostic hypoxia-associated gene set in IDH-mutant glioma - Dao Trong, Huy Philip; Rösch, Saskia; Mairbäurl, Heimo; Pusch, Stefan; Unterberg, Andreas; Herold-Mende, Christel; Warta, Rolf (International journal of molecular sciences, 2018)
Glioma growth is often accompanied by a hypoxic microenvironment favorable for the induction and maintenance of the glioma stem cell (GSC) phenotype. Due to the paucity of cell models of Isocitrate Dehydrogenase 1 mutant (IDH1mut) GSCs, biology under hypoxic conditions has not been sufficiently studied as compared to IDH1 wildtype (IDH1wt) GSCs. We therefore grew well-characterized IDH1mut (n = 4) and IDH1wt (n = 4) GSC lines under normoxic (20%) and hypoxic (1.5%) culture conditions and harvested mRNA after 72 h. Transcriptome analyses were performed and hypoxia regulated genes were further analyzed using the expression and clinical data of the lower grade glioma cohort of The Cancer Genome Atlas (LGG TCGA) in a confirmatory approach and to test for possible survival associations. Results show that global expression changes were more pronounced in IDH1wt than in IDH1mut GSCs. However, when focusing on known hypoxia-regulated gene sets, enrichment analyses showed a comparable regulation in both IDH1mut and IDH1wt GSCs. Of 272 significantly up-regulated genes under hypoxic conditions in IDH1mut GSCs a hypoxia-related survival score (HRS-score) of five genes (LYVE1, FAM162A, WNT6, OTP, PLOD1) was identified by the Least Absolute Shrinkage and Selection Operator (LASSO) algorithm which was able to predict survival independent of age, 1p19q co-deletion status and WHO grade (II vs. III) in the LGG TCGA cohort and in the Rembrandt dataset. Altogether, we were able to identify and validate a novel hypoxia-related survival score in IDH1mut GSCs consisting of five hypoxia-regulated genes which was significantly associated with patient survival independent of known prognostic confounders.